Preparation method and application of ternary thermoelectric gel electrolyte based on bacterial nanocellulose
By adding GdmCl and LiCl to the bacterial nanocellulose hydrogel, a ternary thermoelectric gel electrolyte with excellent thermoelectric properties and mechanical properties was prepared, which solved the problem of degradation in traditional gel thermal batteries in harsh environments and achieved higher thermoelectric properties and stability.
Patent Information
- Application Number
- CN202510061723.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Traditional gel thermal batteries are prone to water loss or freezing in harsh environments, resulting in structural damage and degradation of performance, and their tensile strength is low, and their thermoelectric coefficient and effective ionic conductivity are insufficient.
Using a ternary thermoelectric gel electrolyte based on bacterial nanocellulose, the electrolyte material with excellent thermoelectric properties, anti-drying properties, anti-freeze properties and excellent mechanical properties is formed by adding the thermosensitive crystallizer GdmCl and the supporting electrolyte LiCl to the bacterial nanocellulose hydrogel.
It achieves high thermal electrical coefficient, anti-freeze and drying and high mechanical strength, expands the working temperature range, and improves overall stability and performance sustainability.
Smart Images

Figure HDA0005243085090000011 
Figure HDA0005243085090000012 
Figure HDA0005243085090000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gel thermoelectric electrolyte materials, and in particular to a preparation method of a ternary thermoelectric gel electrolyte based on bacterial nanocellulose and an application thereof in a gel thermoelectric battery. Background Art
[0002] With the development of industry, human society has long been constrained by energy crises and environmental problems. In the future, these traditional energy sources based on fossil fuels (including coal, oil, and natural gas) will face exhaustion. In addition, burning these fossil fuels will inevitably produce waste heat, as well as a variety of low-grade heat such as solar heat and human body heat. Therefore, thermoelectric materials that collect low-grade heat and directly convert it into electrical energy have received great attention. Traditional semiconductor thermoelectric generators rely on the electronic Seebeck effect and face challenges such as high cost, potential toxicity, and low Seebeck coefficient (usually less than 400 μV K -1 ) and other limitations. In contrast, ionic thermoelectric generators not only have a higher thermoelectric coefficient (S i ), usually more than 1mV K -1 , and has a simpler structure and lower cost, which makes it have a wider application prospect.
[0003] Thermal batteries are a type of thermoelectric generator based on redox reactions, which directly convert ionic current into electronic current through redox reactions, thereby achieving continuous operation with higher energy density. However, aqueous thermal batteries are prone to electrolyte leakage and have safety issues. Gel thermal batteries provide a safe, simple, and scalable direct thermal-electric energy conversion method by encapsulating liquid electrolytes in a gel matrix, and are expected to become the first choice for emerging thermoelectric generators. With their continuous working mode and adaptability to dynamic human-machine interfaces, gel thermal batteries show great application potential in self-powered wearable electronics, especially in the context of the rapidly expanding Internet of Things (IoT). However, the gel network affects the solvation structure and mass transfer of redox pairs, usually resulting in smaller S e In addition, conventional gel thermal batteries, such as those based on polyacrylamide (PAAM) or polyvinyl alcohol (PVA), have low tensile strengths ranging from 8 to 240 kPa and are prone to water loss or freezing in harsh environments, leading to irreversible structural damage and performance degradation. Therefore, it is urgent to develop high-performance gel thermal batteries with excellent thermoelectric performance, high stability, and superior mechanical robustness to meet the growing demand for wearable flexible electronic devices. Summary of the invention
[0004] In view of the above-mentioned problems currently existing in gel thermoelectric battery electrolytes, the present invention provides a method for preparing a ternary thermoelectric gel electrolyte based on bacterial nanocellulose. By adding a thermosensitive crystallizer GdmCl and a supporting electrolyte LiCl to a bacterial nanocellulose hydrogel containing a redox couple of K3Fe(CN)6 and K4Fe(CN)6, the electrolyte material has excellent thermoelectric properties, anti-drying properties, anti-freezing properties and outstanding mechanical properties.
[0005] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0006] A method for preparing a ternary thermoelectric gel electrolyte based on bacterial nanocellulose comprises the following steps:
[0007] Step 1, stirring potassium ferrocyanide K3Fe(CN)6 and potassium ferrocyanide K4Fe(CN)6 in deionized water until dissolved, to obtain solution A; then adding lithium chloride LiCl to solution A and stirring until completely dissolved, to obtain solution B;
[0008] Step 2, slicing the bacterial nanocellulose NC hydrogel and soaking it in the solution B in step 1 to obtain a solution C containing the NC hydrogel;
[0009] Step 3: Add guanidine chloride GdmCl to solution C containing NC hydrogel obtained in step 2, slowly stir to make crystalline particles appear inside the hydrogel, then let it stand at room temperature for aging, take it out and dry it with nitrogen until the surface moisture is removed, to obtain a ternary thermoelectric gel electrolyte based on bacterial nanocellulose.
[0010] Preferably, in solution B, the concentrations of potassium ferrocyanide, potassium ferrocyanide and lithium chloride are 0.25-0.4 mol / L, 0.25-0.4 mol / L and 1-4 mol / L respectively.
[0011] Preferably, in step 2, the soaking time is 16 to 24 hours to ensure that Fe(CN)6 3- Ion, Fe(CN)6 4- Ions and Li + Ions can fully penetrate into the interior of the hydrogel.
[0012] Preferably, the molar ratio of guanidine chloride to potassium ferrocyanide in step 3 is 1-3:0.4, within which the Fe(CN)6 4- Ions fully crystallize with guanidine chloride without affecting Fe(CN)6 3- ions. If the ratio is higher than 3:0.4, it will cause Fe(CN)6 3- The ions also crystallize, reducing the thermoelectric coefficient.
[0013] Preferably, in step 3, the slow stirring speed is 50-200 rpm and the stirring time is 1-2 hours to ensure that crystallization occurs inside the gel. If there is no stirring or the stirring speed is too high, crystallization will basically appear in the solution phase, resulting in poor crystallization effect inside the gel.
[0014] Preferably, in step 3, the static aging time is 12 to 24 hours, so that the crystalline particles in the gel can fully grow and be evenly distributed in the gel.
[0015] Preferably, steps 1 to 3 are carried out in a light-proof environment to avoid the decomposition of potassium ferrocyanide K3Fe(CN)6 and potassium ferrocyanide K4Fe(CN)6 to produce toxic substances.
[0016] The bacterial nanocellulose-based ternary thermoelectric gel electrolyte prepared in the present invention can be used in gel thermal batteries.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] The present invention prepares a thermoelectric electrolyte material with high thermoelectric performance, antifreeze and anti-drying performance and high mechanical strength by adding a thermosensitive crystallizer GdmCl and a supporting electrolyte LiCl to a bacterial nanocellulose hydrogel containing a redox couple of K3Fe(CN)6 and K4Fe(CN)6. GdmCl selectively induces K4Fe(CN)6 to form thermosensitive crystals, so that Fe(CN)6 3- / 4- The concentration difference increases, resulting in a higher thermoelectric coefficient. On this basis, adding LiCl as a supporting electrolyte, Li + The strong electronic attraction destroys the hydrogen bond network in the gel system, significantly reduces the minimum operating temperature of the electrolyte, expands the operating temperature range, and keeps the gel moist by capturing water molecules in the atmosphere, thereby improving the overall stability. Therefore, the ternary thermoelectric gel electrolyte (denoted as Li-TCNT) prepared by the present invention obtains excellent thermoelectric performance, antifreeze and anti-drying properties, and excellent mechanical properties. This work helps to understand how the addition of LiCl and GdmCl affects the performance of thermal batteries at the molecular level, and provides a simple and effective strategy for the development of high-performance gel thermal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the Fourier transform infrared spectrum of Li-TCNT prepared in Example 1 of the present invention;
[0020] Figure 2 It is the UV-visible spectrum after GdmCl is added to K3Fe(CN)6 and K4Fe(CN)6 solutions respectively in Example 1 of the present invention;
[0021] Figure 3is the X-ray diffraction pattern of the Li-TCNT inner crystalline particles prepared in Example 1 of the present invention;
[0022] Figure 4 is a differential scanning calorimetry spectrum of Li-TCNT prepared in Example 1 of the present invention;
[0023] Figure 5 is the steady-state voltage-temperature difference-time curve of Li-TCNT prepared in Example 1 of the present invention;
[0024] Figure 6 is the current-voltage-power curve of Li-TCNT prepared in Example 1 of the present invention under different temperature gradients;
[0025] Figure 7 is the cycle stability of Li-TCNT prepared in Example 1 of the present invention at -10°C;
[0026] Figure 8 The TCNT obtained in Comparative Example 1 of the present invention ( Figure 8 (a)) and Li-TCNT obtained in Example 1 ( Figure 8 (b)) Optical photo comparison;
[0027] Fig. 9 The weight loss curves of the TCNT obtained in Comparative Example 1 of the present invention and the Li-TCNT obtained in Example 1 are compared;
[0028] Fig.10 The TCNT obtained in Comparative Example 1 of the present invention ( Fig.10 (a)) and Li-TCNT obtained in Example 1 ( Fig.10 (b)) Raman spectrum comparison;
[0029] Fig.11 It is a comparison of stress-strain curves of TCNT obtained in Comparative Example 1 of the present invention and Li-TCNT obtained in Example 1;
[0030] Fig.12 The TCNT obtained in Comparative Example 1 of the present invention ( Fig.12 (a)) and Li-TCNT obtained in Example 1 ( Fig.12 (b)) comparison of job stability;
[0031] Fig.13 The TCNT obtained in Comparative Example 1 of the present invention ( Fig.13 (a)) and Li-TCNT obtained in Example 1 ( Fig.13 (b)) Comparison of optical images at low temperature. DETAILED DESCRIPTION
[0032] In order to further illustrate the present invention, the preparation method and application of a bacterial fiber nanocellulose ternary thermoelectric gel electrolyte provided by the present invention are described in detail below in combination with the embodiments and illustrated in combination with the accompanying drawings, but it should not be understood as limiting the scope of protection of the present invention.
[0033] Example 1
[0034] In this example, a ternary thermoelectric gel electrolyte based on bacterial nanocellulose was prepared according to the following steps, and the following steps were performed in a light-proof environment:
[0035] Step 1: Dissolve 2.633g K3Fe(CN)6 in 20mL deionized water, then add 2.947g K4Fe(CN)6 and stir magnetically at room temperature for 20min to completely dissolve it, to obtain solution A, which is dark yellow in color. Add 2.543g LiCl to solution A, stir magnetically at room temperature for 20min to completely dissolve LiCl, to obtain solution B.
[0036] Step 2: Cut the NC hydrogel into slices of 15 mm×15 mm×2 mm, remove the moisture from the surface of the slices, immerse them in solution B in step 1, and let them stand at room temperature for 24 hours to obtain solution C containing NC hydrogel.
[0037] Step 3: Add 5.732 g of GdmCl powder to solution C containing NC hydrogel obtained in step 2, slowly stir at 200 rpm for 1 hour, then stand at room temperature for 12 hours to allow it to completely crystallize, take it out and dry it with nitrogen until the surface moisture is removed to obtain Li-TCNT gel electrolyte.
[0038] Figure 1 This is the Fourier transform infrared spectrum of Li-TCNT obtained in this example, at 3400 cm -1 The strong absorption peak at 1160cm -1 The absorption peak at 2040 cm is the asymmetric glucose COC stretching vibration. -1 and 2115cm -1 The absorption peaks at 4- and Fe(CN)6 3- The C≡N stretching vibration at 3185cm -1 and 1580cm -1 The absorption peak at is attributed to the stretching vibration of NH and CN, indicating the successful construction of the ternary gel electrolyte.
[0039] In order to verify the ability of guanidine chloride to induce crystallization, K3Fe(CN)6 and K4Fe(CN)6 solutions with a concentration of 0.4 mol / L were prepared, and then GdmCl was added thereto to different concentrations (1 M to 4 M). Figure 2 The UV-visible spectra of K3Fe(CN)6 and K4Fe(CN)6 solutions after adding GdmCl respectively. As can be seen from the figure, GdmCl selectively induces the crystallization of K4Fe(CN)6.
[0040] Figure 3 This is the X-ray diffraction pattern of the crystalline particles in Li-TCNT obtained in Example 1. Compared with the pure samples of K3Fe(CN)6, K4Fe(CN)6 and GdmCl, it can be seen that the crystalline particles are mainly composed of GdmCl and K4Fe(CN)6.
[0041] Figure 4 This is the differential scanning calorimetry spectrum of the Li-TCNT obtained in this example. As can be seen from the figure, the freezing point of Li-TCNT is -33.1°C, indicating that the lowest operating temperature of the thermal battery is widened to -33.1°C.
[0042] Figure 5 This is the steady-state voltage-temperature-time curve of Li-TCNT obtained in this example. As shown in the figure, the thermoelectric coefficient of Li-TCNT reaches 3.42mVK -1 .
[0043] Figure 6 The current-voltage-power curves of Li-TCNT obtained in this example under different temperature gradients are shown in the figure. As can be seen from the calculation, when the temperature difference is 5, 10, 15 and 20 °C, the power density reaches 0.060, 0.254, 0.630 and 1.102 W m, respectively. -2 .
[0044] Figure 7 This is the cycle stability of the Li-TCNT obtained in this example at -10°C. It can be seen that the voltage remains stable after multiple cycles at low temperature, indicating good low-temperature stability.
[0045] Comparative Example 1
[0046] This comparative example prepares TCNT material according to the following steps, which are carried out in a light-proof environment:
[0047] Step 1: First, dissolve 2.633 g of K3Fe(CN)6 in 20 mL of deionized water, and then add 2.947 g of K4Fe(CN)6 and stir magnetically at room temperature for 20 min to completely dissolve it to obtain solution A. The color of the solution is dark yellow.
[0048] Step 2: Cut the NC hydrogel into slices of 15 mm×15 mm×2 mm, remove the moisture from the surface of the slices, and then immerse them in solution A of step 1 and stand at room temperature for 24 hours to obtain solution C containing NC hydrogel.
[0049] Step 3: Add 5.732 g of GdmCl powder to solution C containing NC hydrogel obtained in step 2, slowly stir at 200 rpm for 1 hour, and then stand at room temperature for 12 hours to allow it to completely crystallize, thereby obtaining a thermosensitive crystallized nanocellulose-based gel thermal battery, recorded as TCNT.
[0050] Figure 8 TCNT obtained in Comparative Example 1 ( Figure 8 (a)) and Li-TCNT obtained in Example 1 ( Figure 8 (b) Optical photo comparison. The surface of TCNT is dry, while the surface of Li-TCNT is wet, indicating that Li-TCNT can spontaneously capture moisture in the air and has the characteristic of anti-drying.
[0051] Fig. 9 The weight loss curves of the TCNT obtained in Comparative Example 1 and the Li-TCNT obtained in Example 1 are compared. After exposure to atmospheric conditions (25°C, RH~40%) for 48 hours, the mass retention rate of Li-TCNT is 55%, while the mass retention rate of TCNT is only 20% after significant drying.
[0052] Fig.10 TCNT obtained in Comparative Example 1 ( Fig.10 (a)) and Li-TCNT obtained in Example 1 ( Fig.10 (b) Raman spectra comparison. TCNT mainly shows a large number of ordered tetrahedral hydrogen bond configurations, and the content of single donor hydrogen bond configurations inside Li-TCNT increases significantly, indicating that the addition of LiCl destroys the ordered hydrogen bond network structure.
[0053] Fig.11 Comparison of stress-strain curves of TCNT obtained in comparative example 1 and Li-TCNT obtained in example 1. The toughness of TCNT is 302 kJ m -3 The toughness of Li-TCNT is 346 kJ m -3 , indicating the improved mechanical strength of Li-TCNT.
[0054] Fig.12 TCNT obtained in Comparative Example 1 ( Fig.12 (a)) and Li-TCNT obtained in Example 1 ( Fig.12 (b) Comparison of working stability. Li-TCNT continuously generates a stable voltage of about 83 mV for more than 1 h at a temperature of 25.5 K, while TCNT has difficulty maintaining a stable voltage at a constant temperature.
[0055] Fig.13 TCNT obtained in Comparative Example 1 ( Fig.13 (a)) and Li-TCNT obtained in Example 1 ( Fig.13(b) Comparison of optical images at low temperatures. Li-TCNT can remain unfrozen at -20°C, while TCNT is completely frozen at -20°C.
[0056] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ternary thermoelectric gel electrolyte based on bacterial nanocellulose, characterized in that: The following steps are involved: Step 1, stirring potassium ferrocyanide K3Fe(CN)6 and potassium ferrocyanide K4Fe(CN)6 in deionized water until dissolved, to obtain solution A; then adding lithium chloride LiCl to solution A and stirring until completely dissolved, to obtain solution B; Step 2, slicing the bacterial nanocellulose NC hydrogel and soaking it in the solution B in step 1 to obtain a solution C containing the NC hydrogel; Step 3: Add guanidine chloride GdmCl to solution C containing NC hydrogel obtained in step 2, slowly stir to make crystalline particles appear inside the hydrogel, then let it stand at room temperature for aging, take it out and dry it with nitrogen until the surface moisture is removed, to obtain a ternary thermoelectric gel electrolyte based on bacterial nanocellulose.
2. The preparation method according to claim 1, characterized in that: In solution B, the concentrations of potassium ferrocyanide, potassium ferrocyanide and lithium chloride are 0.25-0.4 mol / L, 0.25-0.4 mol / L and 1-4 mol / L, respectively.
3. The preparation method according to claim 1, characterized in that: In step 2, the soaking time is 16 to 24 hours to ensure that Fe(CN)6 3- Ion, Fe(CN)6 4- Ions and Li + Ions can fully penetrate into the interior of the hydrogel.
4. The preparation method according to claim 1, characterized in that: In step 3, the molar ratio of guanidine chloride to potassium ferrocyanide is 1-3:0.
4.
5. The preparation method according to claim 1, characterized in that: In step 3, the rotation speed of slow stirring is 50-200 rpm, and the stirring time is 1-2 h.
6. The preparation method according to claim 1, characterized in that: In step 3, the standing aging time is 12 to 24 hours, so that the crystal particles in the gel can fully grow and be evenly distributed in the gel.
7. The preparation method according to claim 1, characterized in that: Steps 1 to 3 are performed in a light-proof environment.
8. A ternary thermoelectric gel electrolyte based on bacterial nanocellulose prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the bacterial nanocellulose-based ternary thermoelectric gel electrolyte according to claim 8 in a gel thermal battery.
Citation Information
Patent Citations
Antifreeze hydrogel as well as preparation method and application thereof
CN110760152A
Preparation method and application of high-performance thermoelectric hydrogel based on ion conduction
CN113881068A
Gel electrolyte with wide temperature range, preparation method of gel electrolyte, aqueous zinc ion battery and application of aqueous zinc ion battery
CN118173916A
Hydrogel electrolyte, preparation method thereof and thermal battery
CN118970221A
Biomass gel thermal battery capable of simultaneously collecting multiple clean energy sources and preparation method of biomass gel thermal battery
CN118973361A